Detailed Numerical Simulation of Planar Liquid Sheet Atomization: Instability Dynamics, Ligament Formation, and Self-Destabilization Mechanisms - Ziting Zhao; Chenglin Zhou; Jianfeng Zou; Jiaqi Sun; Yufeng Yao (Fire)
The primary atomization of planar liquid sheets near nozzle exits plays a critical role in the study of pressure-swirl atomizers, yet its intrinsic destabilization and breakup mechanisms remain insufficiently characterized due to the multi-scale nature of gas–liquid interactions, significantly limiting the predictive capacity of current widely adopted atomization models. This study utilizes three-dimensional direct numerical simulations (DNSs) with adaptive mesh refinement and the Volume-of-Fluid (VOF) method to examine the instability and disintegration of a spatially developing planar liquid sheet under operating conditions representative of aero-engine combustors (thickness <semantics>h=100 μm</semantics>, <semantics>We=2544</semantics>, <semantics>Re=886</semantics>). Adaptive grid resolution (minimum cell size <semantics>2.5 μm</semantics>) enables precise resolution of multi-scale interface dynamics while maintaining mass conservation errors below 0.1‱. High-fidelity simulations reveal distinct atomization cascades originating from the jet tip, characterized by liquid sheet roll-up, interface expanding, interface tearing, and ligament/droplet formation. Through extraction and surface characterization of representative shed liquid ligaments, we quantify temporal and spatial variations between ligaments propagating toward and away from the jet core region. Key findings demonstrate that ligament impingement on the liquid core serves as the dominant mechanism for surface wave destabilization, surpassing the influence of initial gas–liquid shear at the nozzle exit. Spectral analysis of upstream surface waves reveals a pronounced correlation between high-wavenumber disturbances and the mean diameter of shed ligaments. These results challenge assumptions in classical atomization models (e.g., LISA) by highlighting self-destabilization mechanisms driven by droplet–ligament interactions. This work provides critical insights for refining engineering atomization models through physics-based ligament diameter prediction criteria.